The Chiastic Structure and Meaning of Paul’s Letter to Philemon - Heil, John Paul (Biblica, 2001)
This article proposes a new chiastic structure for Paul’s letter to Philemon based on rigorous criteria and methodology. The center and pivot of the chiasm, ‘but without your consent I resolved to do nothing, so that your good might not be as under compulsion but rather under benevolence’ (v. 14), is a key to explicating the letter’s supposedly unclear purpose. Paul wants Philemon to give his former slave Onesimus back to Paul as a beloved brother and fellow worker for the gospel of Jesus Christ, because of Philemon’s response to the grace of God evident in his faithful love for the holy ones as a beloved brother and fellow worker of Paul.